Coexpression analysis of a large-scale transcriptome identified a calmodulin-like protein regulating the development of adventitious roots in poplar. (24th June 2020) - Xiao, Zheng'ang; Zhang, Yan; Liu, Meifeng; Zhan, Chang; Yang, Xiaoqing; Nvsvrot, Tashbek; Yan, Zhaogui; Wang, Nian
Abstract: Poplars are important woody plants, and the ability to form adventitious roots (ARs) is the key factor for their cultivation because most poplars are propagated by cloning. In previous studies, Ca 2+ was confirmed to regulate AR formation in poplar. In this study, wild-type poplar cuttings grown in 1.0 mM Ca 2+ solution showed the best visible performance of AR development. Coexpression analysis of a large-scale RNA-Seq transcriptome was conducted to identify Ca 2+ -related genes that regulate AR development in poplar. A total of 15 coexpression modules (CMs) were identified, and two CMs showed high association with AR development. Functional analysis identified a number of biological pathways, including 'oxidation-reduction process', 'response to biotic stimulus' and 'metabolic process', in tissues of AR development. The Ca 2+ -related pathway was specifically selected, and its regulation in poplar AR development was predicted. A Ca 2+ sensor, PdeCML23-1, which is a member of the calmodulin-like protein (CML) family, was found to promote AR development by phenotypic assay of overexpressed PdeCML23-1 transgenic lines at various growing conditions. By measuring cytosolic Ca 2+ in AR tips, PdeCML23-1 seemed to play a role in decreasing cytosolic Ca 2+ concentration. Additionally, the expression profiles of some genes and phytohormone indole acetic acid (IAA) were also changed in the overexpressed PdeCML23-1 transgenic lines. According to this study, we were able to provide a global view of gene regulation for poplar AR development. Moreover, we also observed the regulation of cytosolic Ca 2+ concentration by PdeCML23-1, and this regulation was involved in AR development in poplar. We also predicted that PdeCML23-1 possibly regulates AR development by modulating IAA content in poplar.